Risk of All-Cause Mortality in Mild Chronic Obstructive Pulmonary Disease: Evidence From the NHANES III and 2007–2012 - Zou W; Ou J; Wu F; Xiao S; Deng Z; Li H; Wang Z; Tang G; Liu S; Ye D; Zhu D; Hu J; et al. (International Journal of COPD)
Weifeng Zou,1,2,* Jie Ou,1,2,* Fan Wu,3,4,* Shan Xiao,5 Zhishan Deng,3 Haiqing Li,3 Zihui Wang,3 Gaoying Tang,3 Shuling Liu,1 Dong Ye,6 Dongshuang Zhu,2 Jinxing Hu,1 Pixin Ran3,4 1State Key Laboratory of Respiratory Disease, Guangzhou Chest Hospital, Guangzhou, People’s Republic of China; 2Department of Pulmonary and Critical Care Medicine, Shufu County People’s Hospital, Kashgar region, Xinjiang, People’s Republic of China; 3State Key Laboratory of Respiratory Disease & Guangzhou Institute of Respiratory Health & National Clinical Research Center for Respiratory Disease & National Center for Respiratory Medicine, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 4Guangzhou National Laboratory, Guangzhou, People’s Republic of China; 5Department of Pulmonary and Critical Care Medicine, Shenzhen Longgang District Central Hospital, Shenzhen, People’s Republic of China; 6Department of Internal Medicine, Guangdong Province Second People’s Hospital, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fan Wu; Pixin Ran, State Key Laboratory of Respiratory Disease & Guangzhou Institute of Respiratory Health & National Center for Respiratory Medicine & National Clinical Research Center for Respiratory Disease & The First Affiliated Hospital of Guangzhou Medical University, 195 Dongfeng Xi Road, Guangzhou, 510120, People’s Republic of China, Email wu.fan@vip.163.com; pxran@gzhmu.edu.cnBackground: It is unclear whether patients with Global Initiative for Chronic Obstructive Lung Disease stage 1 (mild) chronic obstructive pulmonary disease (COPD) have a higher risk of all-cause mortality than participants with normal spirometry results.Methods: We used the data from the National Health and Nutrition Examination Survey (NHANES) III and 2007– 2012, which included participants aged 20– 79 years, to investigate whether patients with mild COPD (whole population and subgroups) have a higher risk of all-cause mortality than participants with normal spirometry. Mild COPD was defined as prebronchodilator forced expiratory volume in 1 second /forced vital capacity < 0.70 and FEV1 ≥ 80% of the predicted value. All-cause mortality risk is the total risk of death from all causes over a given period of time. We performed subgroup analyses by sex, age, smoking status, race, body mass index, and level of education. We also performed sensitivity analyses using the lower limit of normal to define COPD.Results: 1,760 patients (64.5% male; median aged 59 years) with mild COPD and 19,969 participants with normal spirometry (46.9% male; median aged 43 years) were followed up (median 308 months). Patients with mild COPD had a higher all-cause mortality risk than participants with normal spirometry (adjusted: Hazard Ratios 1.13, 95% Confidence Intervals 1.04– 1.23; P = 0.005). The results remained robust in the sensitivity analyses. The subgroup analyses results for male sex, age ≥ 50 years, and current smokers were consistent with the main analysis.Conclusion: Patients with mild COPD had a higher all-cause mortality risk than those with normal spirometry, especially males, those aged ≥ 50 years, and current smokers. These results suggest the need for appropriate management of different subgroups with mild COPD.Keywords: mild COPD, all-cause mortality, chronic obstructive pulmonary disease, COPD